Evaluasi Pengalaman Pengguna dan Perbaikan Rancangan Antarmuka Pengguna Sistem Informasi Akademik Mahasiswa Universitas Brawijaya - Renaldi Sidiq Wibowo; Ismiarta Aknuranda; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Sistem Informasi Akademik Mahasiswa Universitas Brawijaya (SIAM UB) is one of the information system services that is useful for managing student academic data. During the system development life cycle, it is necessary to evaluate the system. However, until now, there has been no research that evaluates or improves the design of the SIAM UB website when accessed via a desktop computer. In this study, an evaluation was carried out using the User Experience Questionnaire (UEQ) to determine the level of user experience and usability testing to understand the problem more deeply. The initial evaluation resulted in the conclusion that SIAM UB can meet the needs of users in obtaining academic information. However, there are still some problems. The evaluation results are used as the basis for improving the user interface design of SIAM UB. User Centered Design (UCD) is used as an approach in making design improvements and evaluations. UCD has four stages, namely understanding and determining the context of use, determining user requirements, creating design solutions, and evaluating designs. This UCD cycle runs for three iterations to produce a design solution in the form of a high-fidelity prototype. Then the high-fidelity prototype was evaluated using usability testing and UEQ. In general, the evaluation results of usability and UEQ testing on high-fidelity prototypes show a positive value and are better than the results of the current evaluation of SIAM UB.